HUBUNGAN MINAT MEMBACA DENGAN KEMAMPUAN DOKKAI MAHASISWA SEMESTER VI PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU TAHUN AKADEMIK 2020/2021 - Sarah Azizah; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aimed to explain the correlation between reading interest and Dokkai ability. This research activity conducted at Japanese Language Study Program FKIP Universitas Riau in the even semester in academic year 2020/2021. This research belonged to correlational research with a quantitative approach. The sample was the sixth-semester students of Japanese Language Study Program FKIP Universitas Riau with the total number of sample was 34 students. The sample selected by using the census method. The instrument was a reading interest questionnaire and a Dokkai ability test. IBM SPSS 25.0 used to process the data. The data analyzed by using Pearsons' correlation analysis technique and regression analysis technique. The result of data analysis concluded that there was a positive and significant correlation between reading interest and Dokkai ability of sixth-semester students of Japanese Language Education Study Program FKIP Universitas Riau with the percentage was 15 percent.Key Words: Reading Interest, Japanese Language, Dokkai Ability